Синтез гвинтових конвеєрів з можливостями технологічного перетворення і мобільної зміни траєкторії перевантаження матеріалів - Гевко, Ів. Б.; Гудь, В. З.; Гевко, Ив. Б.; Hevko, I.; Hud, V. (ЦНТУ, 2019)
При проведенні морфологічного синтезу визначено відповідну кількість складових елементів конструкцій конвеєрів та зв’язків між ними, які визначають їх певні конструктивні ознаки. На основні виконаного аналізу складено морфологічну матрицю з морфологічними ознаками елементів генерованих конструкцій гвинтових конвеєрів. Згенеровано значну кількість працездатних конструкцій гвинтових конвеєрів з окремими типами функціональних операцій чи призначенням. Також розроблено класифікацію гвинтових конвеєрів з можливостями технологічного перетворення і мобільної зміни траєкторії перевантаження матеріалів. При проведении морфологического синтеза определено соответствующее количество составляющих элементов конструкций конвейеров и связей между ними, которые определяют их определенные конструктивные признаки. На основные выполненного анализа составлено морфологическую матрицу с морфологическими признаками элементов генерируемых конструкций винтовых конвейеров. Создано значительное количество трудоспособных конструкций винтовых конвейеров с отдельными типами функциональных операций или назначений. Также разработана классификация винтовых конвейеров с возможностями технологического преобразования и мобильного изменения траектории перегрузки материалов. The purpose of the article is to carry out the synthesis by the method of hierarchical grouping by means of morphological analysis of screw conveyors with the possibilities of technological transformation and mobile change of the trajectory of material overload. The appropriate number of constituent elements of the conveyor structures and the relationships between them that determine their particular design features are determined. The basic analysis is based on a morphological matrix with the morphological features of the elements of the generated constructions of the screw conveyors and the connections between them. A considerable number of functional screw conveyor structures with separate types of functional operations or purpose, which are multifunctional and efficient compared to traditional screw conveyors, have been developed and investigated. The classification of screw conveyors with the possibility of technological transformation and mobile change of the trajectory of material overload is also developed. Structural synthesis of screw conveyors with the possibilities of technological transformation and mobile change of the trajectory of material overload by structural hierarchical grouping was performed by means of morphological analysis and a certain number of their variants was generated according to 9 types. It is also determined that individual technological operations or functional features, which are inherent in screw conveyors with the possibility of technological transformation and mobile trajectory change, can be combined into one design, which will allow to obtain multifunctional designs of conveyors.
Синтез винтовых конвейеров с возможностями технологического преобразования и мобильного изменения траектории перегрузки материалов
Synthesis of Screw Conveyors with the Possibilities of Technological Transformation and Mobile Change of the Trajectory of Material Overload
Keywords: синтез; гвинтовий конвеєр; морфологічний аналіз; винтовой конвейер; морфологический анализ; synthesis; screw conveyor; morphological analysis